The Usefulness of a Multidisciplinary Team Approach in Decision Making For Pancreatic Serous Cystic Neoplasms - Ricci, Claudio; Casadei, Riccardo; Taffurelli, Giovanni; Ingaldi, Carlo; D’Ambra, Marielda; Pacilio, Carlo Alberto; Pagano, Nico; Calculli, Lucia; Serra, Carla; Santini, Donatella; et al. (JOP. Journal of the Pancreas, 2014)
Context Serous cystic neoplasms of the pancreas are regarded as benign entities with rare malignant potential and are frequently resected. Objective The purpose of the study was to evaluate the usefulness of a multidisciplinary team (MDT) approach in decision making regarding the diagnosis and management of pancreatic serous cystic neoplasms. Methods A retrospective study of a prospective database involving 43 patients with serous cystic neoplasms was carried out. Patients who underwent multidisciplinary team evaluation (Group 1) were compared with patients who did not (Group 2) as regards demographic, clinical, radiological, surgical and pathological data. Uni-multivariate analyses were carried out. Results Uni-multivariate analysis showed that a multidisciplinary team approach was significantly related to the type of management, suggesting that MDT evaluation independently reduced the odds of surgery (odds ratio (OR) 0.1; 95% confidence interval (CI) 0.02-0.8; P=0.027). Age, second level imaging techniques, latero-lateral diameter, cranio-caudal diameter and Wirsung duct size differed between the two groups; however, the differences were not statistically significant. Conclusions A multidisciplinary team approach seems to be useful in proper decision making regarding the diagnosis and management of pancreatic serous cystic neoplasms. Image: Multidisciplinary team.